The synergistic action of phosphate and interleukin-6 enhances senescence-associated calcification in vascular smooth muscle cells depending on p53. (September 2019) - Xu, Deping; Zeng, Fanjun; Han, Linzi; Wang, Jun; Yin, Zongzhi; Lv, Liying; Guo, Liyu; Wang, Deguang; Xu, Yuanhong; Zhou, Haisheng
Highlights: Phosphate inducing senescence-associated calcification is concerned with up-regulating p53 expression. IL-6 induces senescence-associated calcification through activating IL-6/sIL-6/STAT3/p53/p21 signaling pathway. The synergistic action of phosphate and IL-6 enhances senescence-associated calcification in a p53-dependent manner. The synergistic action of phosphate and IL-6 is inhibited by anti-aging agents in a dose-dependent manner. Abstract: Cardiovascular calcification is associated with cardiovascular morbidity and mortality of patients with end-stage renal diseases (ESRD). Hyperphosphatemia and many of the inflammatory markers and mediators, including interleukin-6 (IL-6), are considered as the major risk factors of cardiovascular calcification. Although cellular senescence may be involved in cardiovascular calcification caused by phosphate overload and (or) IL-6 in patients with ESRD, less is known about the underlying mechanisms for phosphate- and IL-6-induced senescence-associated calcification of vascular smooth muscle cells (VSMCs). In the present study, we investigated the correlation between cellular senescence and vascular calcification induced by loading phosphate and (or) IL-6 in VSMCs. Our findings show that p53 plays a major role in senescence-associated vascular calcification induced by phosphate overload. IL-6 induces senescence-associated calcification in VSMCs depending upon activation of the IL-6/soluble IL-6 receptor (sIL-6R)/signal transducer and activator of transcription 3 (STAT3)/p53/p21 pathway. We demonstrate that the synergistic action of phosphate overload and IL-6 enhances senescence-associated calcification in a p53-dependent manner and is inhibited by an anti-aging agent (resveratrol) in a dose-dependent manner.